Peptide-Drug Conjugates and Their Targets in Advanced Cancer Therapies - Hoppenz, Paul; Els-Heindl, Sylvia; Beck-Sickinger, Annette G. (Frontiers in Chemistry, 2020)
Cancer became recently the leading cause of death in industrialized countries. Even though standard treatments achieve significant effects in growth inhibition and tumor elimination, they cause severe side effects as most of the applied drugs exhibit only minor selectivity for the malignant tissue. Hence, specific addressing of tumor cells without affecting healthy tissue is currently a major desire in cancer therapy. Cell surface receptors, which bind peptides are frequently overexpressed on cancer cells and can therefore be considered as promising targets for selective tumor therapy. In this review, the benefits of peptides as tumor homing agents are presented and an overview of the most commonly addressed peptide receptors is given. A special focus was set on the bombesin receptor family and the neuropeptide Y receptor family. In the second part, the specific requirements of peptide-drug conjugates (PDC) and intelligent linker structures as an essential component of PDC are outlined. Furthermore, different drug cargos are presented including classical and recent toxic agents as well as radionuclides for diagnostic and therapeutic approaches. In the last part, boron neutron capture therapy as advanced targeted cancer therapy is introduced and past and recent developments are reviewed.